PERANCANGAN DAN PEMBUATAN WEBSITE PUSKESMAS NOGOSARI DENGAN MENGGUNAKAN METODE WATERFALL - Haris Hammaminata; Feby Erawantini; Novita Nuraini; Gamasiano Alfiansyah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Submission of information at Nogosari Public Health Center was done by sticking announcements in the cornerof the wall and bulletin board. Nogosari Public Health Center’s queue registration system was still offline-based.People could only get this information and take the queue if they came to the public health center. This researchaimed to design and create Nogosari Public Health Center’s website using waterfall method. The approach ofthis research was Research and Development (R & D). Data collection techniques used interviews andobservations. The analysis unit of this research were the head of the Nogosari Public Health Center Jember, ahealth promotion officer, an environmental health officer, a surveillance officer, a KIA-KB-Nutrition serviceofficer, a medical record officer, and 2 patients in Nogosari Public Health Center Jember. The results showedNogosari Public Health Center’s website accompanied by additional features include online queuing features,suggestion box facilities, and question and answer pages. Suggestions from researchers are the system shouldbe developed into an integrated service system by adding customize features to existing services. NogosariPublic Health Center Jember need a domain host so that this website can be accessed by the internet.